PUBLIC SERVICE DELIVERY IN INDONESIA'S OUTER ISLANDS: A PERFORMANCE EVALUATION - Ponto, Iriane Sosiawaty; Waisapy, Jeanly; Fadli, Zul (Universitas 17 Agustus 1945 Surabaya, 2025)
This study evaluates the performance of Civil State Apparatus personnel in delivering public services in Kairatu Barat Sub-district, West Seram Regency, a remote archipelagic region in Eastern Indonesia. Using a sequential explanatory mixed-methods design, the research involved 94 respondents comprising 37 Civil State Apparatus staff and 57 community service recipients. Data collection employed structured questionnaires and in-depth interviews to obtain comprehensive perspectives on public service quality. Findings reveal that Civil State Apparatus performance is generally categorized as good, with work precision emerging as the primary strength (score: 3.92). However, significant weaknesses exist in service innovation (score: 3.51). From the community perspective, staff friendliness received the highest appreciation (score: 3.88), reflecting the internalization of local cultural values of